TRANSISI FASA TITATNIUM OKSIDA MELALUI KONDENSASI EX-SITU HIDROGEN TITANAT TIPE STRUKTUR LEPIDOKSROSIT - Hari Sutrisno; Sunarto Sunarto (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2010)
The objectives of the research are to study of the structure type of titanium dioxide (TiO2) obtained form the ex-situ condensation of hydrated hydrogen titanates with the structure type of lepidocrocite. Hydrated hydrogen titanates were obtained by ion exchabge of H+ for Cs+ in cesium titanates by 1 M HCl solution by Chimie Douce method. The results show that TiO2 (B), anatase, and anatase-rutile mixture were obtained heat treatment of hydrated hydrogen titanate at 100, 200, 300, 500, and 600oc respectively. The powders were characterized by X-rays diffractometer (XRD), High Resolution Scanning Electron Microscopy (HRSEM) and High Resolution Transmission Electron Microscopy (HRTEM). The research indicated that the protonic titanate, H0.54 Ti1.865 0.135O4 0.5H2O ( =vacancy), lost the interlayer water by being heated up to 200oC to produce a dehydrated phase, H0.54 Ti1.865 0.135O4. Above 300oC, the dehydrated phase completely transformed to TiO2(B) and anatase was obtained as pure phase at 600oC. The phase transformed as the following process: H0.54Ti1.865 0.135O4 0.5H2O à H0.54Ti1.865 0.135O4 0.25H2Oà H0.54Ti1.865 0.135O4 à TiO2(B) à TiO2-anatase.